2018
DOI: 10.1080/1828051x.2018.1532326
|View full text |Cite
|
Sign up to set email alerts
|

Previous alpine grazing experience of cows has little medium-term effect on feeding behaviour, milk yield and composition in a traditional alpine system

Abstract: Berard (2019) Previous alpine grazing experience of cows has little medium-term effect on feeding behaviour, milk yield and composition in a traditional alpine system,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…In contrast to our hypothesis, the 3 breeds did not perform differently the day after the moving treatments, although their global performance throughout the experiment was different. Valdostana Red Pied cows had the lowest milk yield (Table 4), even lower than that observed by Niero et al (2018) and Koczura et al (2019a) in late-lactating Valdostana Red Pied cows, although their cows had been fed 2 kg of concentrate/d, unlike the cows in the present study. Montbéliarde did not produce less milk per day than Holstein cows, in contrast to what Pires et al (2015) observed in an extensive grazing system.…”
Section: Lack Of Difference In Responses Of Breed Types To Moving Treatmentscontrasting
confidence: 76%
See 1 more Smart Citation
“…In contrast to our hypothesis, the 3 breeds did not perform differently the day after the moving treatments, although their global performance throughout the experiment was different. Valdostana Red Pied cows had the lowest milk yield (Table 4), even lower than that observed by Niero et al (2018) and Koczura et al (2019a) in late-lactating Valdostana Red Pied cows, although their cows had been fed 2 kg of concentrate/d, unlike the cows in the present study. Montbéliarde did not produce less milk per day than Holstein cows, in contrast to what Pires et al (2015) observed in an extensive grazing system.…”
Section: Lack Of Difference In Responses Of Breed Types To Moving Treatmentscontrasting
confidence: 76%
“…Milk produced on mountain pastures has a higher fat content and is particularly rich in beneficial functional fatty acids. However, it also has a lower protein content and sometimes less favorable cheesemaking properties (Hauswirth et al, 2004;Leiber et al, 2005;Koczura et al, 2019a). Studies involving the effect of transhumance on milk and cheese quality on a seasonal scale have shown that milk yield decreases on highland pastures and SCC increases (Zendri et al, 2016;Niero et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The somatic cell count was determined by a fluorimetric method (Fossomatic 5000, Foss Electric, Hillerød, Denmark). The remaining milk was frozen and stored at −20 °C until being analyzed for FA, according to Koczura et al [27]. In order to determine rennet coagulation properties, two replicates of 10 ml of fresh milk were added to 200 µL of a freshly prepared 2% v / v rennet solution (Caglio Clerici 1:10,000 with 80% chymosin and 20% pepsin, Como, Italy), following the rennet concentration used for the production of Fontina PDO cheese.…”
Section: Methodsmentioning
confidence: 99%